2019
DOI: 10.3390/su11102800
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits and Sustainable Food Production in the Development of Innovative “Healthy” Snacks

Abstract: In recent years, science about nutrition and food technology has grown enormously. These advances have provided information about the human body’s need for certain nutrients and the impact of human nutrition on quality of life and health. New technologies enable the production of many new products that meet the expectations of food consumers. To meet the challenges posed by consumers, food producers are developing new food products that are included in the next generation food. Changing nutritional trends forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 90 publications
(133 reference statements)
0
32
0
4
Order By: Relevance
“…Recently, consumers are more interested in sustainable food production, owing to the growing awareness of environmental pollution and the high amount of waste generated during conventional food processing. Moreover, they are searching for food products with improved safety, as well as healthy aspects [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, consumers are more interested in sustainable food production, owing to the growing awareness of environmental pollution and the high amount of waste generated during conventional food processing. Moreover, they are searching for food products with improved safety, as well as healthy aspects [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence the food industry’s focus on developing healthy fruit snacks, which could provide consumers with nutrient-dense energy snacks. Healthy snacks are defined as snacks containing a high number of beneficial ingredients that have a positive effect on human health, and usually well-balanced nutrients [ 2 ]. Dried fruits are considered a healthier alternative to popular snacks rich in sugar or salt and the recommendations for their consumption are constantly present in the dietary guidelines of many countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azeredo et al [9] demonstrated six months' shelf life without preservatives for mango fruit leathers with low water activity (0.62), low pH (3.8), and a moisture content of 17.2%. Furthermore, although low moisture content can extend shelf life by preventing the fruit leathers from inhibiting microbial growth, the texture of the fruit leathers can be negatively affected due to extensive crispiness of the product [43,44]. The sugar content was 40.85 g/100 g-about 6.12 g of sugar for three servings of one fruit bar (5 g).…”
Section: Proximate Analysis Of Mango-natal Plum Fruit Leather (Mn2)mentioning
confidence: 99%
“…The authors would like to make the following correction to the published paper [1]. The change is as follows:…”
mentioning
confidence: 99%